Dežela senc Spomin na izgon in izginotje judovske skupnosti v Prekmurju - Luthar, Oto (ZRC SAZU, Založba ZRC, 2015)
The Land of Shadows was first conceived as a complementary resource for History classes in Slovenian high schools. It served to complement to the patchy Holocaust teaching resources. It consists of two parts: the first part features a historical overview of anti-Semitism and eventually the Holocaust in Europe, which is followed by an account of the situation in Slovenia. The authors relied on the life-story of Mrs Erika Fürst, one of the Holocaust survivors from Prekmurje, Slovenia. In creating a compelling and touching narrative, the authors used visual material from the archives and from various publications depicting the period and the problematic, notably excerpts from two graphic novels: Art Speigelman's Maus, Jason Lutes' Berlin.